Strategi Pengembangan Pariwisata Berkelanjutan Di Kawasan Karst - Nugraeni, Galih; Sumarni, Sumarni; Pujiati, Heri Roh (Musamus Journal of Public Administration, 2024)
Purpose — The purpose of this study is to explore the strategies adopted by Pokdarwis in developing tourism in karst areas so as to avoid damaging the environment. Method — Qualitative description with a case study approach, data collection using interviews, observation and documentation. Result — Tourism development that uses a sustainable tourism system can protect karst areas because the concept of sustainable tourism is different from the concept of mass tourism where the concept of sustainable tourism prioritises environmental protection over material benefits. There are several strategies carried out divided into three categories, the first is environmental management by limiting visitors, making SOPs in accordance with tourism management standards in karst areas, maintaining cleanliness, being careful in involving investors. The second is Socio-Cultural by socialising invisible beliefs, maintaining culture related to community beliefs, conducting cultural titles, more "humanist" counters. The third is the Local Economy with the Pokdarwis strategy consisting of local people, traders who participate in the tourist area are local people, the distribution of results prioritises the welfare of the community